Implementation of The Analytical Hierarchy Process (AHP) Method for The Selection of Achieving Students at Universitas Nahdlatul Ulama Sunan Giri - M. Ivan Ariful Fathoni; Dwi Nurul Hidayati; Anisa Fitri (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
Universitas Nahdlatul Ulama Sunan Giri (UNUGIRI) has many students who have achievements. The number of outstanding students is a problem in determining the decision-making of outstanding students. One of the effective decision-making methods for solving problems in selecting outstanding students is the Analytical Hierarchy Process (AHP) method. The AHP method in this study considers four criteria: Grade Point Average, Writing Paper, Achievement (Non-Academic), and SPEKMA points. Out of 73 UNUGIRI students who had achievements, a ranking was carried out into ten alternative students. The results of calculating ten alternatives based on four criteria with the AHP method obtained the highest score of 0.1437 for students with the name PWA. Based on these results, PWA can be designated as outstanding students for the 2021/2022 academic year.